Kardio-Onkologie - Lehmann, Lorenz; Bokemeyer, Carsten; Müller, Oliver J. (De Gruyter, 2023)
How does one prevent potential cardiotoxic injury in oncological treatment? Shared risk factors with cardiovascular illnesses may complicate the treatment of cancer, and standard cardiology treatment procedures may have devastating side effects in oncology patients. Improved oncology treatments and the uncertain cardiovascular side effects of cancer therapies demand a sophisticated understanding of the new field of cardio-oncology
Keywords: Aufsatzsammlung; Nebenwirkung; Komplikation; Kardiovaskuläre Krankheit; Therapie; Krebs